Mechanical properties of metal-ceramic nanolaminates: Effect of constraint and temperature. (1st January 2018) - Yang, L.W.; Mayer, C.; Li, N.; Baldwin, J.K.; Mara, N.A.; Chawla, N.; Molina-Aldareguia, J.M.; Llorca, J.
Abstract: Al/SiC nanolaminates with equal nominal thicknesses of the Al and SiC layers (10, 25, 50 and 100 nm) were manufactured by magnetron sputtering. The mechanical properties were measured at 25 °C and 100 °C by means of nanoindentation and micropillar compression tests and the deformation mechanisms were analyzed by in situ micropillar compression tests in the transmission electron microscope. In addition, finite element simulations of both tests were carried out to ascertain the role played by the strength of the Al layers and by the elastic constraint of the ceramic layers on the plastic flow of Al in the mechanical response. It was found that the mechanical response was mainly controlled by the constraint during nanoindentation or micropillar compression tests of very thin layered (≈10 nm) laminates, while the influence of the strength of Al layers was not as critical. This behavior was reversed, however, for thick layered laminates (100 nm). These mechanisms point to the different effects of layer thickness during nanoindentation and micropillar compression, at both temperatures, and showed the critical role played by constraint on the mechanical response of nanolaminates made of materials with a very large difference in the elasto-plastic properties. Graphical abstract: Image 1